Effects of exogenous plant regulators on growth and development of “Kyoho” grape under salt alkali stress - Zhao, Maoxiang; Li, Jiajia; Shi, Xiangneng; Sanaullah Malik, M.; Quan, Yi; Guo, Dinghan; Wang, Lei; Wang, Shiping (Frontiers in Plant Science, 2023)
Salinity is one of the major abiotic stresses besides drought and cold stress. The application of plant growth regulators (PGRs) is an effective method to mitigate yield losses caused by salinity. However, we investigated the effects of exogenous regulatory substances (γ-aminobutyric acid (GABA), salicylic acid (SA), and brassinolide (BR) on the growth and development of “Kyoho” grapevine under salt stress. The results showed that exogenous regulators GABA, SA, and BR alleviated the inhibition of grape growth by saline stress and regulated the effects of salinity stress on grape fruit development and quality. All three regulators significantly increased fruit set, cross-sectional diameter, weight per unit, and anthocyanin content. In conclusion, this study provides a theoretical basis for grape production practices by using exogenous aminobutyric acid (GABA), salicylic acid (SA), and brassinolide (BR) to mitigate the hazards of salinity stress.